Effects of Dietary Ferulic Acid on the Intestinal Microbiota and the Associated Changes on the Growth Performance, Serum Cytokine Profile, and Intestinal Morphology in Ducks - Liu, Yang; Lin, Qian; Huang, Xuan; Jiang, Guitao; Li, Chuang; Zhang, Xu; Liu, Shengli; He, Lingyun; Liu, Yali; Dai, Qiuzhong; Huang, Xingguo (Frontiers in Microbiology, 2021)
The present study investigated the effects of ferulic acid (FA) on the growth performance, serum cytokine profile, intestinal morphology, and intestinal microbiota in ducks at the growing stage. 300 female Linwu ducks at 28 d of age with similar body weights were randomly divided into 5 groups. Each group contained 6 replicates of 10 birds. The dietary treatments were corn-soybean-based diet supplemented with FA at the concentrations of 0, 100, 200, 400 and 800 mg/kg diet. The results demonstrated that 200, 400 and 800 mg/kg FA increased the average daily gain (P = 0.01), 400 and 800 mg/kg FA increased the final body weight (P = 0.02), 100, 200 and 800 mg/kg FA increased the serum glutathione (P = 0.01), and 100, 400 and 800 mg/kg FA increased the glutathione peroxidase activities in birds (P < 0.01). Additionally, 200, 400 and 800 mg/kg FA lowered the serum levels of interleukin-2 (P = 0.02) and interleukin-6 (P = 0.04). Moreover, the morphometric study of the intestines indicated that 400mg/kg FA decreased the crypt depth in jejunum (P = 0.01) and caecum (P = 0.04), and increased the ratio of villus height to crypt depth in jejunum (P = 0.02). Significant linear and/or quadratic relationships were found between FA concentration and the measured parameters. FA increased the populations of genera Faecalibacterium, Paludicola, RF39, and Faecalicoccus in cecum (P < 0.05), whereas decreased the populations of Anaerofilum and UCG-002 (P < 0.05). Phylum Proteobacteria were negatively, but order Oscillospirales, and family Ruminococcaceae were positively related to the parameters of the growth performance. Phylum Bacteroidetes, class Negativicutes and family Rikenellaceae were negatively associated with the parameters of the antioxidative capability. And phylum Cyanobacteria, Elusimicrobia, and Bacteroidetes, class Bacilli, family Rikenellaceae, and genus Prevotella were positively associated with the parameters of the immunological capability. Thus, it was concluded that the supplementations of 400 to 800 mg/kg FA in diet could inprove the growth performance, antioxidative and immunological capabilities, intestinal morphology, and modulated the gut microbial construction of Linwu ducks at the growing stage.